A Bacterial Enrichment Study and Overview of the Extractable Lipids from Paleosols in the Dry Valleys, Antarctica: Implications for Future Mars Reconnaissance - Hart, K.M.; Szpak, M.T.; Mahaney, W.C.; Dohm, J.M.; Jordan, S.F.; Frazer, A.R.; Allen, Christopher; Kelleher, B.P. (Astrobiology, 2011)
The Dry Valleys of Antarctica are one of the coldest and driest environments on Earth with paleosols in selected areas that date to the emplacement of tills by warm-based ice during the Early Miocene. Cited as an analogue to the martian surface, the ability of the Antarctic environment to support microbial life-forms is a matter of special interest, particularly with the upcoming NASA/ESA 2018 ExoMars mission. Lipid biomarkers were extracted and analyzed by gas chromatography-mass spectrometry to assess sources of organic carbon and evaluate the contribution of microbial species to the organic matter of the paleosols. Paleosol samples from the ice-free Dry Valleys were also subsampled and cultivated in a growth medium from which DNA was extracted with the explicit purpose of the positive identification of bacteria. Several species of bacteria were grown in solution and the genus identified. A similar match of the data to sequenced DNA showed that Alphaproteobacteria, Gamma-proteobacteria, Bacteriodetes, and Actinobacteridae species were cultivated. The results confirm the presence of bacteria within some paleosols, but no assumptions have been made with regard to in situ activity at present. These results underscore the need not only to further investigate Dry Valley cryosols but also to develop reconnaissance strategies to determine whether such likely Earth-like environments on the Red Planet also contain life.